On some questions of the criminal-legal and criminal-procedural reglamentation of the detention of the person suspected been criminal - Laptsevich, Irina I. (Journal of the Belarusian State University. Law, 2019)
The presented article analyzes the theoretical criminal-legal and criminal-procedural aspects of the arrest of the person who committed the crimes, the concepts «crime» and «socially dangerous act», «criminal» and «person who committed a socially dangerous act» are correlated. The opinions of scientists on the mentioned problems are explored, the experience of the Russian Federation is studied. The author proposes his own point of view on resolving contradictions in the Criminal Code and Criminal Code of Procedurs of the Republic of Belarus, justifying the need for correcting criminal and criminal procedural laws, making proposals to improve legislation.
Keywords: detention of a person; causing harm; crime; socially dangerous act; insanity; punishment; circumstances precluding the crime of the act